PENGARUH CORPORATE GOVERNANCE, INVESTMENT OPPORTUNITY SET DAN KUALITAS LABA TERHADAP NILAI PERUSAHAAN PADAPERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSAEFEK INDONESIA PERIODE 2018-2023 - Ginting, Yessa Patricia; Pasaribu, Dompak; Situmorang, Duma Rachel (MTU PRESS, 2024)
This study aims to analyze the influence of corporate governance proxied by Managerial Ownership, investment opportunity set proxied by Market to Book Value of Asset and earnings quality proxied by Earnings Quality on company value proxied by Price to Book Value. A population of 47 banking companies listed on the Indonesian Stock Exchange, 11 companies were used as samples in this research. The sampling technique used is the purposive sampling method. Research data was obtained from the website www.idx.co.id and the company's official website. Then the data obtained was processed using the SPSS version 27 application. The research results showed that managerial ownership partially had a positive but not significant effect on Price to Book Value. Market to Book Value of Assets partially has a positive and significant effect on Price to Book Value. Earnings quality partially has a positive but not significant effect on Price to Book Value. Managerial ownership, Market to Book Value of Assets, and earnings quality simultaneously have a significant effect on Price to Book Value. The adjusted R square value is 0.935 or 93.5%, which means the research variable is able to explain Price to Book Value which is determined by Managerial Ownership, Market to Book Value of Assets, and Profit Quality by 93.5% while the remaining 6.5% is influenced by other factors outside this research.